A CODE MIXING ANALYSIS ON EFL STUDENTS' CASUAL CONVERSATION AT SCHOOL - Ni Kadek Ayu Rinawati (Universitas Pendidikan Ganesha, 2020)
ABSTRACT This qualitative research aimed at analyzing the types of code mixing are used by students and find out the reasons underlined the use of code mixing in the students’ interaction. It is investigated using the theory of Suwito to know the kind of code mixing they might use (form of words, phrase, hybrid, repetition word, idioms or clauses). The subjects of this research were the first year students in SMK Mahkota Wisata Rendang. In this research, the researcher used two methods, namely questionnaire and interview. Questionnaire purposed to know how the students interact each other, whether they do code mixing by adding English or not; where and when they mostly do code mixing. There were five teen students involved for this questionnaire. Meanwhile, the interview was conducted for six students (three of male and three female) in order to examine the students’ motivates in doing code mixing between different genders. The result showed that students do code mixing in their communication with their friends at school. Phrase insertion is 50%, word insertion is also often used for 26%, hybrid insertion is 8%, repetition word insertion is 4%, idioms insertion is 4% and clauses insertion is 4%. They are frequently use phrase insertion and word insertion in communication, rather than those four insertions. Keyword : Code mixing, students’ interaction ABSTRAK Penelitian kualitatif ini bertujuan untuk menganalisis tipe campur kode (code mixing) yang digunakan siswa pada umumnya dan juga mengetahui alasan yang melatarbelakangi mereka melakukan campur kode dalam interaksinya sehari-hari di sekolah. Penelitian ini menggunakan teori dari Suwito yang mana untuk mengetahui kemungkinan jenis campur kode yang mereka gunakan dalam bentuk kata, frasa, penggabungan dua bahasa dalam satu kata, pengulangan kata, idiom dan klausa. Subjek dari penelitian ini adalah siswa kelas 10 di SMK Mahkota Wisata Rendang. Dalam menggali data, penulis menggunakan dua yakni kuisioner dan interview. Kuisioner bertujuan untuk mengentahui bagaiamana siswa berinteraksi dengan siswa lainnya di lingkungan sekolah, apakah mereka menggunakan campur kode dengan mencampur bahasa pertama mereka dengan bahasa Inggris atau tidak, kapan dan dimana mereka biasanya melakukan interaksi dengan menggunakan campur kode ini. Dalam melakukan kuisioner, ada 15 siswa yang dilibatkan. Sementara pada sesi interview, penulis melibatkan 3 siswa laki-laki dan 3 siswa perempuan dengan tujuan untuk mengetahui motivasi mereka dalam melakukan campur kode dengan jenis kelamin yang berbeda. Hasil penelitian menunjukkan bahwa siswa sering melakukan campur kode dalam berinteraksi dengan temannya di sekolah. Campur frasa sebanyak 50%, campur kata 26%, penggabungan dua bahasa dalam satu kata 8%, pengulangan kata 4%, idiom 4% dan klausa sebanyak 4%. Mereka lebih sering menggunakan campur frasa dan kata jika dibandingkan dengan keempat tipe campur kode yang lain. Keyword : campur kode, interaksi siswa